Calculation of weighted averages approach for the estimation of ping tolerance values - Silalom S. (2014)
A biotic index was created and proposed as a tool to assess water quality in the Upper Mae Ping sub-watersheds. The Ping biotic index was calculated by utilizing Ping tolerance values. This paper presents the calculation of Ping tolerance values of the collected macroinvertebrates. Ping tolerance values were estimated by a weighted averages approach based on the abundance of macroinvertebrates and six chemical constituents that include conductivity, dissolved oxygen, biochemical oxygen demand, ammonia nitrogen, nitrate nitrogen and orthophosphate. Ping tolerance values range from 0 to 10. Macroinvertebrates assigned a 0 are very sensitive to organic pollution while macroinvertebrates assigned 10 are highly tolerant to pollution.